The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1103/physrevb.72.024504
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of two-band superconductors: The case ofMgB2

Abstract: Thermodynamic properties of the multiband superconductor MgB 2 have often been described using a simple sum of the standard BCS expressions corresponding to σ-and π-bands. Although, it is a priori not clear if this approach is working always adequately, in particular in cases of strong interband scattering. Here we compare the often used approach of a sum of two independent bands using BCS-like α-model expressions for the specific heat, entropy and free energy to the solution of the full Eliashberg equations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 70 publications
5
26
0
2
Order By: Relevance
“…In the clean limit, one sees two different excitation gaps for the two bands. In accord with earlier calculations for s ++ superconductors [20], the interband impurity scattering mixes the pairs in the two bands, so that the states appear in the a-band at the energy range of the b-band gap. These states are gradually filled in with increasing scattering rate.…”
Section: Density Of States In Superconductive Statesupporting
confidence: 84%
See 1 more Smart Citation
“…In the clean limit, one sees two different excitation gaps for the two bands. In accord with earlier calculations for s ++ superconductors [20], the interband impurity scattering mixes the pairs in the two bands, so that the states appear in the a-band at the energy range of the b-band gap. These states are gradually filled in with increasing scattering rate.…”
Section: Density Of States In Superconductive Statesupporting
confidence: 84%
“…Interband scattering is expected to modify the gap functions and the tunneling DOS in the superconducting state in a multiband superconductor. In the weak coupling regime the impurity effects have been discussed in [19] within the Born limit and extended in [20] to the strong coupling case. In the following, we will calculate the gap functions, and the superconducting DOS by solving the nonlinear Eliashberg equations in the s ± and s ++ superconductors for various values of the interband nonmagnetic scattering rate, going beyond the Born approximation.…”
Section: Density Of States In Superconductive Statementioning
confidence: 99%
“…One, therefore, certainly needs to check other self-consistent models to compare the results. In this scenario, within the framework of the Eliashberg approach for MgB 2 Dolgov et al 53 have shown that the α model is sufficiently accurate to find the superconducting gap values, although the gap's partial contribution lacks full agreement. Another recently proposed γ model by Kogan et al 54 is also an effective approach that takes into account the interband pairing potential and is successfully tested for two band superconductors, MgB 2 and V 3 Si.…”
Section: Resultsmentioning
confidence: 99%
“…Since Moskalenko [1,2] Suhl et al [3] introduced the twoband model that accounts for multiple energy bands in the vicinity of the Fermi energy contributing electron pairing in superconductor, the two-band model has been applied to high temperature superconductor in copper oxides [4][5][6][7][8][9][10], MgB 2 superconductor [11][12][13], and heavy Fermion superconductor [14,15]. Dolgov et al [16] studied the thermodynamic properties of the two-band superconductor: MgB 2 . The superconducting energy gap, free energy, the entropy, and heat capacity were calculated within the framework of twoband Eliashberg theory.…”
Section: Introductionmentioning
confidence: 99%